PENGEMBANGAN BUKU SYARAT KECAPAKAN UMUM PRAMUKA GOLONGAN PENEGAK SEBAGAI PENGUATAN SOFTSKILL BERBICARA - Dhea Eriza Silvyawati; Benedictus Sudiyana; Dewi Kusumaningsih (Universitas Negeri Makassar, 2023)
This study aims to develop the general proficiency requirements book for rover scout and find out the validity of the book that has been developed to improve speaking soft skills. This research uses Research and Development (R&D) with the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation). The instruments used in this study were observation guidelines, interview guidelines, and questionnaires. Data analysis techniques in this study used quantitative analysis techniques and qualitative analysis techniques. The results of this study show the product development process of the Public Enforcement Requirements Book of General Proficiency as an Aspect of Language Development. The development of this book goes through five stages, namely analysis, design, development, implementation, and evaluation. The test results on students who were members of the scouts were 30 students and obtained a responsse percentage of 89.0% and was categorized as